2017
DOI: 10.3945/cdn.117.001644
|View full text |Cite
|
Sign up to set email alerts
|

Enriching the Starter Diet in n–3 Polyunsaturated Fatty Acids Reduces Adipocyte Size in Broiler Chicks

Abstract: Epidemiologic studies associate perinatal intake of eicosapentaenoic acid (EPA, 20:5n–3) and docosahexaenoic acid (DHA, 22:6n–3) with reduced adiposity in children, suggesting that these fatty acids may alter adipose tissue development. The objective of this study was to determine whether enriching the perinatal diet in EPA and DHA reduces fat deposition in young chicks. Cobb 500 broiler chicks were fed isocaloric diets containing fat (8% wt:wt) from fish oil (FO), lard, canola oil, or flaxseed oil from 7 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…It is worth mentioning that in SOY, as well as in EP diets, the predominant type of FA belongs to the long-chain PUFA, which can effectively regulate body fat by increasing the volume of adipocytes. 62,63 As previously mentioned, the EP group had elevated level of TGs in the serum. Indeed, an increased deposition of LCFAs in WAT, principally in the form of TGs, can result from increased LCFA synthesis or uptake, augmented conversion of LCFA to TGs, reduced LCFA oxidation, or changes in the TG lipolysis which in turn decreases TG or LCFAs removal.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is worth mentioning that in SOY, as well as in EP diets, the predominant type of FA belongs to the long-chain PUFA, which can effectively regulate body fat by increasing the volume of adipocytes. 62,63 As previously mentioned, the EP group had elevated level of TGs in the serum. Indeed, an increased deposition of LCFAs in WAT, principally in the form of TGs, can result from increased LCFA synthesis or uptake, augmented conversion of LCFA to TGs, reduced LCFA oxidation, or changes in the TG lipolysis which in turn decreases TG or LCFAs removal.…”
Section: Discussionmentioning
confidence: 54%
“…Both SOY and EP diets displayed cellular hypertrophy, compared with the CTRL group, shown as a decrease in the number of adipocytes. It is worth mentioning that in SOY, as well as in EP diets, the predominant type of FA belongs to the long‐chain PUFA, which can effectively regulate body fat by increasing the volume of adipocytes . As previously mentioned, the EP group had elevated level of TGs in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Other than promoting bone quality, n-3 PUFA also decrease adipose tissue in part due to the shared developmental origin of adipocytes and osteoblasts, both of which originate during embryonic development from mesenchymal stem cells [24]. Dietary EPA and DHA supplementation suppressed the differentiation and maturation of adipocytes, resulting in lower fat accretion in humans, mammals, and broilers [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, fish oil supplementation in breeder hen diet potentially alleviates excess fat deposition and bone weakness in offspring broilers [3]. Work by Liu et al [18] using quail supports the potential to developmentally program bone quality through fish oil in the hen diet, and extensive evidence from several studies in other species indicated the maternal dietary EPA and DHA are not only associated with lower fat accretion but also better bone quality in offspring [14,[25][26][27][28][39][40][41][42]. Maternal supplementation of fish oil in broiler breeder hens decreased adiposity in offspring broiler chicks compared to those hatched from hens fed fatty acids from corn oil (an n-6 PUFA-rich oil) [43].…”
Section: Introductionmentioning
confidence: 99%
“…For example, supplementing broiler diets with flaxseed oil (10%) reduced abdominal fat by 30% compared to equivalent amounts of saturated or monounsaturated fatty acids ( Ferrini et al, 2008 ). Both fish and flaxseed oils have also been shown to reduce adipocyte size in broiler chicks, suggesting that they act relatively early on adipose development ( Torchon et al, 2017 ). The relative effects of fish oil and flaxseed oil as replacements for sunflower oil have also been compared.…”
Section: Introductionmentioning
confidence: 99%